1998
DOI: 10.1136/jnnp.65.5.656
|View full text |Cite
|
Sign up to set email alerts
|

Regional changes in hippocampal T2 relaxation and volume: a quantitative magnetic resonance imaging study of hippocampal sclerosis

Abstract: Objective-The principal MRI features of hippocampal sclerosis are volume loss and increased T2 weighted signal intensity. Minor and localised abnormalities may be overlooked without careful quantitation. Hippocampal T2 relaxation time (HT2) can be quantified, but previously has only been measured on a few thick coronal slices with interslice gaps. In this study HT2 was measured along the entire length of the hippocampus on contiguous slices and used, with quantitative measures of hippocampal volume (HV) and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
105
1
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(117 citation statements)
references
References 26 publications
7
105
1
2
Order By: Relevance
“…These methods have demonstrated considerable efficacy, especially with the addition of T2 relaxation time data. [36][37][38][39][40][41] Patients with mesial temporal lobe epilepsy exhibit smaller hippocampal volumes. 16,[42][43][44][45][46][47] This hippocampal volume reduction is highly concordant with the side of the epileptogenic focus, and hippocampal deficits are most pronounced ipsilateral to the epileptic focus.…”
Section: Temporal Lobe Epilepsymentioning
confidence: 99%
“…These methods have demonstrated considerable efficacy, especially with the addition of T2 relaxation time data. [36][37][38][39][40][41] Patients with mesial temporal lobe epilepsy exhibit smaller hippocampal volumes. 16,[42][43][44][45][46][47] This hippocampal volume reduction is highly concordant with the side of the epileptogenic focus, and hippocampal deficits are most pronounced ipsilateral to the epileptic focus.…”
Section: Temporal Lobe Epilepsymentioning
confidence: 99%
“…Previous studies with dual-echo T2 have given good data for the evaluation of patients. 8,9 More recently, multiecho T2 relaxometry techniques have been introduced at 3T. 10 With the installation of a 3T Excite MR imaging scanner (GE Healthcare, Milwaukee, Wis), we decided to evaluate the improved fast spin-echo (FSE) options with respect to obtaining dual-echo data for the production of calculated T2 maps.…”
mentioning
confidence: 99%
“…It has been shown that measurement of the change in T 2 provides important information about the mobility and chemical environment of the tissues of interest [4], [9] - [11]. Previous studies examining the utility of T 2 mapping in the context of neurologic and psychiatric disease demonstrated variations in T 2 values, sometimes very subtle, in specific brain regions within conditions of autism [12], schizophrenia [13], [14], epilepsy [15], Parkinson's [16], multiple sclerosis [17], [18], Alzheimer disease [9], tumors [19], [20], [21] and a host of other disorders [6], [14], [16], [22], [23]. Nevertheless, mapping the T 2 parameter is rarely used in clinical diagnostics, the most common reported reasons being higher scanning times [4], [6], [10], [11] or its lack of specificity, in contrast to its high sensitivity [5], [6], [17], [24].…”
Section: Introduction N Recent Years Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%
“…Nevertheless, mapping the T 2 parameter is rarely used in clinical diagnostics, the most common reported reasons being higher scanning times [4], [6], [10], [11] or its lack of specificity, in contrast to its high sensitivity [5], [6], [17], [24]. In clinical studies, T 2 relaxation data is most commonly obtained from single-slice MR sequences [15], [24] - [27]. For tissue mapping purposes, a multi-slice sequence is more suitable.…”
Section: Introduction N Recent Years Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%